Traditional Chinese Medicine JianPiHuaTan formula improving quality of life and survival in patients with colorectal cancer through RAS/RAF downstream signaling pathways - He, Jian; Li, Guojun; Wu, Yu; Zhang, Tong; Yao, Mingjiang; Zang, Mingxuan; Zou, Jianhua; Song, Jinjie; Li, Liusheng; Chen, Qian; Cao, Guang; Cai, Linlin (Frontiers in Pharmacology, 2024)
Objective: JianPiHuaTan Formula (JPHTF), a traditional Chinese medicine (TCM), has been utilized as an adjunctive therapy for colorectal cancer (CRC). The study aims to evaluate the potential clinical benefits of JPHTF and its effectiveness in inhibiting tumor growth. Methods: 300 stage II/III CRC patients and 412 advanced CRC patients were enrolled to verify the clinical value of JPHTF in CRC treatment. Furthermore, CRC patient-derived xenograft (PDX) mice were utilized to investigate the regulatory mechanisms of JPHTF. Results: JPHTF significantly improved abdominal distension, shortness of breath, drowsiness, loss of appetite, sleep, and tiredness in stage II/III CRC patients, thereby improving their quality of life. Simultaneously, JPHTF served as a supportive therapy in extending the overall survival (OS) of stage IV CRC patients with RAS/RAF mutations undergoing chemotherapy. Additionally, JPHTF effectively impeded tumor progression in CRC PDX models with RAS mutation, accompanied by a reduction in tumor cell content in the JPHTF group. Transcriptomic analysis revealed the involvement of the Hippo and Hedgehog signaling pathways in JPHTF-mediated CRC inhibition.Furthermore, mice in the JPHTF group exhibited increased immune cell infiltration. Conclusions: These findings suggested that JPHTF may inhibits tumor growth in CRC with RAS mutation by modulating RAS/RAF downstream signaling pathways, specifically the Hippo and Hedgehog signaling, leading to increased immune cell infiltration.